The Model Of Employee Job Involvement And Career Development - Aswad, Andi; Moeins, Anoesyirwan (Green Publisher, 2023)
Using multiple linear regression analysis, this research delves into exploring the effects that job engagement, career growth, and remuneration have on job contentment. Proportionate Random Sampling was the preferred technique for selecting participants, while a survey was the ideal tool for collecting data. The study gathered data via questionnaires from 63 permanent staff of M2M Solutions Ltd. The outcome of the study indicates that job satisfaction is positively affected by job involvement and compensation, while career development has a positive and significant impact on job satisfaction. When considering job involvement, career development, and compensation collectively, an equally positive and significant effect on job satisfaction was observed. Therefore, the three independent variables, job involvement (X1), career development (X2), and compensation (X3), can account for job satisfaction. Job satisfaction is most influenced by compensation, according to the outcome of a regression test.